Penerapan Ice Breaking Siku, Sakit, Sikat Untuk Meningkatkan Antusiasme Siswa Pada Pembelajaran PAI di SMP Roudhlotul Qur’an Rawadadi - Mufiddah, Latifatul; Ikhsanudin, Muhamad; Saiful Amin, Muhammad (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
Student engagement and enthusiasm are essential components of effective learning, particularly in Islamic Religious Education (Pendidikan Agama Islam / PAI), which is often delivered over long instructional periods. In classroom practice, extended lesson duration frequently leads to student boredom, loss of focus, and decreased emotional readiness to learn, thereby reducing the effectiveness of instruction. Although previous studies have discussed the use of ice breaking activities to enhance motivation and classroom atmosphere, limited research has specifically examined contextual, practice-based ice breaking strategies within PAI learning at the junior secondary school level, particularly focusing on students’ emotional enthusiasm rather than academic performance. This study aims to analyze the implementation of the ice breaking “siku, sakit, sikat” activity and its impact on students’ learning enthusiasm in PAI classes at SMP Roudlotul Qur’an Rawadadi. This research employed a qualitative descriptive approach. Data were collected through classroom observations, in-depth interviews with the PAI teacher and students, and documentation of learning activities. The data were analyzed using thematic analysis to identify patterns related to the implementation process, student responses, and supporting and inhibiting factors. The findings indicate that the ice breaking “siku, sakit, sikat” activity effectively functions as a positive pedagogical interruption that restores students’ emotional energy, reduces boredom, and creates a more dynamic and enjoyable classroom atmosphere. Students demonstrated increased enthusiasm, emotional engagement, and social interaction after the activity, although its impact on academic participation such as questioning and discussion remained limited and depended on individual student characteristics. The study concludes that ice breaking “siku, sakit, sikat” plays a significant role in enhancing students’ emotional readiness and enthusiasm for learning PAI. While it does not directly improve academic participation, it provides an important emotional and social foundation that supports more effective learning conditions.